Randomised controlled trial of bariatric surgery versus a community weight loss programme for the sustained treatment of idiopathic intracranial hypertension: the Idiopathic Intracranial Hypertension Weight Trial (IIH:WT) protocol. Issue 9 (27th September 2017) - Ottridge, Ryan; Mollan, Susan P; Botfield, Hannah; Frew, Emma; Ives, Natalie J; Matthews, Tim; Mitchell, James; Rick, Caroline; Singhal, Rishi; Woolley, Rebecca; Sinclair, Alexandra J
Abstract : Introduction: Effective treatments are lacking for idiopathic intracranial hypertension (IIH), a condition characterised by raised intracranial pressure (ICP) and papilloedema, and found primarily in obese women. Weight loss and lowering body mass index (BMI) have been shown to lower ICP and improve symptoms in IIH; however, weight loss is typically not maintained, meaning IIH symptoms return. The Idiopathic Intracranial Hypertension Weight Trial (IIH:WT) will assess whether bariatric surgery is an effective long-term treatment for patients with IIH with a BMI over 35 kg/m 2 . The National Institute for Health and Care Excellence recommends bariatric surgery in people with a BMI over 35 kg/m 2 and a qualifying comorbidity; currently IIH does not qualify as a comorbidity. Methods and analysis: IIH:WT is a multicentre, open-label, randomised controlled clinical trial of 64 participants with active IIH and a BMI over 35 kg/m 2 . Participants will be randomised in a 1:1 ratio to bariatric surgery or a dietary weight loss programme and followed up for 5 years. The primary outcome measure is ICP at 12 months. Secondary outcome measures include ICP at 24 and 60 months, and IIH symptoms, visual function, papilloedema, headache, quality of life and cost-effectiveness at 12, 24 and 60 months. Trial registration number: IIH:WT is registered as ISRCTN40152829 and on ClinicalTrials.gov as NCT02124486 and is in the pre-results stage.